VERBAL HUMOUR CREATED BY NON-OBSERVANCE OF COOPERATIVE PRINCIPLE IN MIRANDA - Bara Yamalita; I Gusti Agung Sri Rwa Jayantini; I Komang Sulatra (Universitas Islam Sumatera Utara (UISU), 2021)
Humour is one of essential aspects to communicate with other people comfortably. Most of verbal humours, especially implicit humours generate because people break Grice’s four conversational maxims. Concerning this phenomenon, this research aims to find out types of non-observance of cooperative principle found in verbal humour, which uttered by the characters in British Situational Comedy Miranda. Qualitative method was adapted to analyze the data, which was conducted through identifying, classifying, interpreting the data. Humorous utterances from nine episodes of Miranda were the primary sources of data. In collecting the data, the researchers observed the whole episodes and the scripts, checked the suitability, took a note, and classified it into tables. The study concludes that there are four types of non-observance of cooperative principle, namely violating, flouting, infringing, and opting out a maxim. The result reveals that there are 80 humorous utterances, which do not obey the maxim. There are 66 utterances (82,5%) of flouting maxim, 10 utterances (12,5%) violation maxim, 3 utterances (3,75%) of infringing maxim, and 1 utterance (1,25%) of opting out maxim which are found in the sitcom.